White Sparse Eyelashes. Issue 4 (July 2018) - Parker, James K.; Jacob, Sharon E.
Abstract : ABSTRACT: Teledermatology is a term to describe the provision of dermatologic medical services through telecommunication technology. This is a teledermatology case of white sparse eyelashes.